RAHMAT LIL-‘ALAMIN DAN PERLAWANAN KEZALIMAN ATAS PALESTINA: ANALISIS PENDEKATAN MAQASHID QUR’AN - Ilham Abiyusuf; Fadhli Maulana Ihsan; Pakhrurrozi Pakhrurrozi; Edi Hermanto (MAHABBAH: Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2026)
This Article examines the concept of rahmatan lil-‘alamin in the Qur’an as an ethical foundation in responding to the humanitarian conflict in Palestine. Amid ongoing oppression, violence, and human rights violations, Qur’anic values such as compassion, justice, forgiveness, and respect for human dignity are often marginalized by political and power interests. The main problem addressed in this research is how the concept of rahmatan lil-‘alamin can be understood through a maqāṣid al-Qur’an approach and its relevance to the Palestine–Israel conflict. This study employs a qualitative approach using library research methods. The primary data consist of QS. Ali Imran [3]:159, Az-Zumar [39]:53, Al-Anbiya [21]:107, and Luqman [31]:18, analyzed through a maqāṣid al-Qur’an perspective with Ibn ‘Āshūr’s At-Taḥrīr wa At-Tanwīr as the main exegetical reference. Secondary data are drawn from academic journals, books, and international human rights reports. The findings indicate that these verses emphasize gentleness, consultation, forgiveness, hope in divine mercy, and the rejection of arrogance and violence in social relations. These values align with the principles of human rights protection, particularly for vulnerable groups such as women and children in Palestine. Therefore, rahmatan lil-‘alamin is not merely a theological concept but also carries social, cultural, and humanitarian implications as a foundation for establishing justice, peace, and human dignity in a prolonged conflict situation Palestine-Israel.